PERAN DAN POTENSI KYAI PESANTREN DALAM PENGEMBANGAN LEMBAGA KEUANGAN SYARIAH DI PEKALONGAN Tinjauan WoM Marketing dan Buzz Marketing - AM. M. Hafidz MS; A. Tubagussurur; Marlina (JURNAL PENELITIAN, 2014)
: Because of their strenght, charisma, knowledge, authority in the boarding school, leverage influentality, expertise, and leverage social networks, Kyai Pesantren have the potential to market the Islamic Financial Institutions by creating buzz and WoM marketing. Their role as marketer could be (1) providing education and learning on Islamic economics, Syaria Islamic Institution and fiqh muamalah (2) building several business units to teach their students operationally and practically on Islamic economics (3) posing as Syaria Supervisory Board in existing Syaria Islamic Institution as Syaria compliance guardian (4) disseminating on Syaria Islamic Institution role to community when giving them a lecture.